Discipline Analysis and Employee Performance - Piatur Pangaribuan; Nasruji Nasruji; Marlina Marlina; Ferdinandus Sampe; Zarkasi Zarkasi (IAIN Palopo, 2023)
This study aims to ascertain the relationship between employee performance and discipline. This research was conducted at PT. Barokah Putra, Jatinangor District. Qualitative research techniques were used in this study. data gathered from speaking with informants. The leaders and staff of PT. Barokah Putra, a total of 7 people, serve as informants in this study. The results of the study show that employee discipline and performance are good enough, but the company still needs to increase the types of compensation given to employees, because it will greatly affect employee discipline. In order to improve performance, training is needed for employees, besides that leaders must carry out better supervision to maintain the quality of the products produced